Use of Indonesian Slang and Equivalents In the Arabic Language - K. Tompunu , Novita; N. Hula, Ibnu Rawandhy (ELOQUENCE : Journal of Foreign Language, 2022)
Background: The exploration of Indonesian slang and its equivalents in the Arabic language offers valuable insights into the dynamics of language use, cultural exchange, and the challenges of translation. Purpose: This study aims to determine the use of slang language and its equivalents in Arabic which is still less popular in everyday speech. This research uses a type of literature research. Method: The data is collected by the method of documentation (input records), then identified and classified according to the type of slang word that is widely used temporally in society. Results and Discussion: The results showed that there were 57 slang words matched in Arabic. 17 nouns, 16 verb- shaped words, 21 adjective-shaped words, and 3 pronoun-shaped words. The slang vocabulary data will continue to grow and develop according to the times and needs, so it has implications for the development of sociolinguistic science because the Slang language was created, and used by certain social groups for internal communication so that what is talked about is not known to others. Conclusions and Implications: this study concludes that slang is an unofficial and non-standard form of language used by adolescents or certain social groups for communication, making it difficult for outsiders to understand and giving it a distinctive character among young people. Slang is widespread in Indonesia, while in Arabic, it is shaped more by the dialects of different countries in the form of Ammiyah language. The study found 57 Indonesian slang words with Arabic equivalents, including 17 nouns, 16 verbs, 21 adjectives, and 3 pronouns. the implications for Arabic language learning emphasize the importance of introducing students to informal language variations like slang, which are commonly used in daily communication by native speakers. Understanding slang in Arabic, influenced by various dialects in the form of Ammiyah, can help students better grasp the cultural and social contexts of the language.